The biopolitics and jus cogen standards: tools for economic law enforcement - Viggiani, Tatiana Sornas [UNESP]; Semeghini Pereira, Marcela Andresa (Fac Meridional-imed, 2015)
Among several analyzed issues by Foucault, bio-power was the one with a greater publicity and into this context appears also bio-politics that has been studied by many authors after Foucault such as Negri. The term bio-politics identifies the way power is transformed in order to govern a population, thus becoming one of the fundamental phenomena of the nineteenth century. However, with the advent of globalization and the expansion of international law, jus cogens standards have been used to control devices and maintain the order in an international society. Therefore, we reach the object of this paper: to analyze the relation between bio-politics and those jus cogens standards. For this paper, we used the deductive method surrounding it by bibliographic and documentary research to reach the conclusion that the use of bio-politics and bio-power are necessary so the jus cogens rules become effective in the international stage, such as being practice and respecting internally in each country. Also, these rules consolidate the dominance of neoliberalism, which deals with the economic aspects as essential, to the harm of social aspects.
Keywords: Bio-politics; Jus cogens; Public international law